2017
DOI: 10.1155/2017/5804860
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective, Pilot Study of De Novo Antidepressant Medication Initiation in Intensive Care Unit Patients and Post-ICU Depression

Abstract: Post-ICU Syndromes (PICS) remain a devastating problem for intensive care unit (ICU) survivors. It is currently unknown if de novo initiation of an antidepressant medication during ICU stay decreases the prevalence of post-ICU depression. We performed a retrospective, pilot study evaluating patients who had not previously been on an antidepressant medication and who were started on an antidepressant while in the trauma surgical, cardiothoracic, or medical intensive care unit (ICU). The PHQ-2 depression scale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…[51][52][53][54] For example, given previous work suggesting the high rates of incomplete or non-response to antidepressants in ICU survivors, clinical trials to test the efficacy of depression-focused psychotherapies to ameliorate cognitive decline could be considered. 51,55 Finally, post-ICU stroke was an independent risk factor for post-ICU cognitive impairment. This could be due to the long-term effects from hypoxic injury from ICU hospitalization causing cerebral hypoperfusion, or from inadequately controlled cardiovascular risk factors leading to post-ICU stroke.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[51][52][53][54] For example, given previous work suggesting the high rates of incomplete or non-response to antidepressants in ICU survivors, clinical trials to test the efficacy of depression-focused psychotherapies to ameliorate cognitive decline could be considered. 51,55 Finally, post-ICU stroke was an independent risk factor for post-ICU cognitive impairment. This could be due to the long-term effects from hypoxic injury from ICU hospitalization causing cerebral hypoperfusion, or from inadequately controlled cardiovascular risk factors leading to post-ICU stroke.…”
Section: Discussionmentioning
confidence: 95%
“…This points to the need to develop targeted therapeutic approaches for depression separate from delirium to prevent dementia in ICU survivors. 51–54 For example, given previous work suggesting the high rates of incomplete or non‐response to antidepressants in ICU survivors, clinical trials to test the efficacy of depression‐focused psychotherapies to ameliorate cognitive decline could be considered 51,55 . Finally, post‐ICU stroke was an independent risk factor for post‐ICU cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors or serotonin–noradrenalin reuptake inhibitor (dual) antidepressants can help manage depressive symptoms in the ICU [ 55 ]. Dual antidepressants have the added benefit of proven efficacy against neuropathic pain [ 56 ].…”
Section: Multimodal Analgesic Therapeutic Approachmentioning
confidence: 99%
“…The effectiveness of classic treatments in the sepsis survivor population is also still in question. For example, a retrospective study showed that the de novo initiation of antidepressant medications in patients who were in treatment before ICU admission did not substantially decrease the prevalence of post-ICU depression [22].…”
Section: Introductionmentioning
confidence: 99%